Ekosistem Kewirausahaan Sebagai Basis Kebijakan Penguatan UMKM di Kabupaten Majene: Sebuah Analisis Kesenjangan Struktural - Hendrawan, Hendrawan; Dewi Nuraliah; Achmad Fauzi Kusmin; Rahmatullah; Muhammad Syihabuddin Taufiq (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the gaps and policy directions for strengthening Micro, Small, and Medium Enterprises (MSMEs) in Majene Regency from the perspective of Entrepreneurial Ecosystem Theory (Stam, 2015). This theoretical approach emphasizes that entrepreneurial success is not only determined by individual entrepreneurs, but also by the systemic interaction between capital, market access, knowledge, talent, social networks, local culture, and institutional and infrastructure support. The study uses a descriptive qualitative method with data collection techniques through literature studies, regional policy documentation, reports from supporting institutions, and triangulation of media data and the latest scientific journals. The results of the study indicate that the MSME entrepreneurial ecosystem in Majene is in the early stages of formation, with various government and institutional interventions such as digital training, Business Development Services programs, and facilitation of export market access through Rumah BUMN. However, significant gaps are still found in aspects of digital access, limited capital and talent, and weak networks between entrepreneurs. Institutional support and physical infrastructure have begun to be built, but have not been integrated into holistic and sustainable MSME development policies. Therefore, a regional policy formulation that is data-based, participatory, and integrated between sectors is needed to strengthen the local entrepreneurial ecosystem in an inclusive manner.